Hydrologic alteration under hydropower dam operations and climate change: a case study in the Sesan River Basin, Lower Mekong Region - Ghalley, Wangmo, author; Niemann, Jeffrey D., advisor; Shrestha, Sangam, advisor; Ettema, Robert, committee member; Poff, N. LeRoy, committee member (Colorado State University. Libraries, 2023)
Hydropower dam developments exacerbated by climate change can significantly disrupt the natural flow regimes, leading to adverse effects on river ecosystems. The Sesan River, a major tributary of the Lower Mekong Basin, is renowned for its diverse biomes and is an important resource for nearby inhabitants. Rapid expansion of hydropower dams has occurred in recent years, but the hydrologic impacts remain poorly understood, particularly when combined with the effects of climate change. This study assessed the hydrologic alterations in Sesan River streamflow due to hydropower dams and potential climate change. Daily streamflow in the Sesan River was simulated using the Hydrologic Engineering Center-Hydrologic Modeling System (HEC-HMS), which was calibrated and evaluated based on streamflow observations. Climate change projections were based on daily precipitation and temperature, which were estimated using an ensemble of three Earth system models from the Coupled Model Intercomparison Project Phase-6 under two Socioeconomic Pathways: SSP2-4.5 (Middle of the road) and SSP5-8.5 (Fossil-fueled development). Future projections spanned 2025 to 2100, which was divided into three 25-year periods called the Near Future (NF), Mid-Future (MF), and Far Future (FF). The projections were compared to a 30-year baseline (BL) period from 1984 to 2014. Results show a consistent rise in both precipitation and temperature for the Sesan basin across all future periods and SSP scenarios. Precipitation is projected to increase by 4% to 13% for SSP2-4.5 and 7% to 29% for SSP5-8.5. Minimum temperature is projected to increase by 8% to 16% for SSP2-4.5 and 10% to 26% for SSP5-8.5, and maximum temperature is projected to increase by 3% to 7% for SSP2-4.5 and 3% to 12% for SSP5-8.5. Hydrologic alterations were assessed using the Range of Variability Approach (RVA) within the Indicators of Hydrologic Alteration (IHA). The impact of dams was assessed by comparing streamflow with dams and without dams during the BL period. The dams significantly altered the hydrograph characteristics by decreasing the high flows and increasing the low flows. The overall alteration due to dams fell within the "moderate" category. The impact of climate change was assessed by comparing streamflow without dams between the BL and the future periods. Climate change increased the high flow rates, with the impact limited to September in the NF but impacting much of the year in the MF and FF periods. Another notable change was the shift in the timing of peak flow from August in the BL to September in the future periods. The hydrologic alteration due to climate change fell within the "low" category. Finally, the combined impact of dams and climate change was assessed by comparing the BL streamflow without dams to future streamflow with dams. Dams were found to mitigate some impacts of climate change by smoothing extreme high flows, especially in the FF period. Overall, the combined impact showed greater alteration than the individual scenarios but fell within the "moderate" category.